WORKPLACE SPIRITUALITY MEMODERASI PENGARUH KOMPLEKSITAS TUGAS DAN LOCUS OF CONTROL PADA KINERJA AUDITOR - Setya Dharma, Nyoman Budhi; Rasmini, Ni Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2022)
The Supreme Audit Agency (BPK) is a high state institution that is free and independent in carrying out its duties. This research was conducted at the BPK RI Representatives of the Province of Bali using primary data obtained from questionnaires. The method of determining the sample using the saturated sample method with respondents obtained as many as 40 people. The data analysis technique used is Moderated Regression Analysis (MRA). The results of the analysis show that task complexity has a negative effect on auditor performance, locus of control has a positive effect on auditor performance, workplace spirituality has a positive effect on auditor performance. The results also show that workplace spirituality weakens the effect of task complexity on auditor performance and workplace spirituality strengthens the effect of locus of control on auditor performance. Suggestions to the leadership of the BPK RI Representatives of the Province of Bali to form a climate of spirituality in the organization by forming a community as a place for sharing among employees so that they can improve their ability to analyze complex tasks.